Startup Control for MMC-HVDC System - WANG Weian; GUI Weihua; TU Qingrui; XU Zheng (Kongzhi Yu Xinxi Jishu)
In order to restrain overvoltage and over current which are produced during the startup process of MMC-HVDC, it is necessary to design startup control for MMC-HVDC system. Based on the topology structure of MMC-HVDC, the methods to charge submodule′ s capacitor of MMC connected source or passive network were studied, and the configuration scheme of limited resistors were designed, thus, startup control strategies for MMC-HVDC system connected two-source or passive network were put forward separately. Simulation results have proved the startup control strategies for MMC-HVDC system to be correct.